Hepatoblastoma: Derived Exosomal LncRNA NEAT1 Induces BMSCs Differentiation into Tumor-Supporting Myofibroblasts via Modulating the miR-132/MMP9 Axis. (8th March 2022) - Hu, Yu; Zai, Hongyan; Jiang, Wei; Ou, Zhenglin; Yao, Yuanbing; Zhu, Qin
Abstract : Background . Hepatoblastoma (HB) is the most common malignant tumor of the liver. MMP9 plays an essential role in HB. The purpose of our study was to screen for differentially expressed lncRNAs and miRNAs that targeted MMP9. Based on this, the role of lncRNA NEAT1/miR-132/MMP9 in HB and the mechanisms involved were discussed. Methods . Bioinformatics analysis was used to screen the differentially expressed lncRNAs and miRNAs targeting MMP9. Exosomes were extracted from HB cells and normal liver cells for characterization and identification. Exosome uptake assay was conducted to determine whether exosomes were absorbed by bone marrow stromal cells (BMSCs). α -SMA, fibronectin, and s-100 expressions in tissues and cells were detected by IHC and ICC. lncRNA XIST, lncRNA NEAT1, miR-132, and MMP9 expressions were characterized by qRT-PCR. Western blot was performed to measure MMP9, α -SMA, and s-100 expressions. Flow cytometry was used to stain α -SMA, s-100. Bioinformatics and dual-luciferase reporter assay were applied to verify the interaction between lncRNA NEAT1 and miR-132, and miR-132 and MMP9. The effect of lncRNA NEAT1 on the development of HB in nude mice was studied. Results . Differentially expressed lncRNA NEAT1/miR-132/MMP9 was obtained through bioinformatics analysis and cell verification. HB-derived exosomal lncRNA NEAT1 regulated miR-132 and MMP9 expression in BMSCs. In addition, HB-derived exosomal lncRNA NEAT1 promoted BMSCs differentiation toward invasive myofibroblast via miR-132/MMP9 axis. LncRNA NEAT1 regulated MMP9 through miR-132. Tumor formation experiments in nude mice showed that HB-derived exosomal lncRNA NEAT1 could affect the development of HB. Conclusion . HB-derived exosomal lncRNA NEAT1 induced BMSCs differentiation into tumor-supporting myofibroblasts via modulating miR-132/MMP9 axis, which provided a new target for HB treatment.